Dental Trauma Caused by Screws in Internal Fixation of Mandibular Osteotomies in the Dog - Verstraete, F. J. M.; Ligthelm, A. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
In a canine mandibular osteotomy model, the extent and nature of dental trauma resulting from internal fixation by means of a plate and screws was investigated. The plate was positioned relatively dorsally on the buccal aspect of the body of the mandible, for maximum biomechanical advantage. After a three-month period, dental trauma was evaluated clinically and histologically. Erosion of the oral mucosa overlying the plate occurred in 10 out of 15 dogs. Dental roots were damaged by 61% of the screws. A variety of lesions involving the periodontal ligament, dentine, cementum, pulp, and periapical tissue were noted. It is concluded that this method of fixation can not be recommended for mandibular fracture repair in the dog.The effects of plating osteotomies of canine mandibles are described and evaluated following a three-month postoperative period.
Keywords: Oral surgery; mandibular fracture; dog